Towards an era of Puhui policy : development and practice of early care and education in China - Zhou, Yu, 1996-; Jiang, Yong, 1973-; Zhu, Xingjian, 1998- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"In China, the puhui early care and education (ECE) program, a national public policy, was officially launched in 2010 to improve the affordability, accessibility, and quality of ECE. Based on a five-year research project, this book explores the development and practice of this ambitious reform campaign with national empirical evidence. The authors evaluate the puhui ECE system (e.g., puhui early education policy, puhui kindergarten services, puhui child care services, and total teacher compensation) from the perspective of universal ECE provision for all children. They focus on children from disadvantaged families such as migrant children, children with special needs, and children from low socio-economic families by emphasizing the targeted provision of ECE based on the principle of educational equity. In addition, they explore the innovative ways to optimize the structure, quality, and efficiency of puhui ECE provision by introducing an innovative provider with the participation of social organizations (China Welfare Institute) and three innovative forms of provision, including village kindergarten, small-scale urban kindergarten, and compensation for children with special needs. The book will be of interest to policy makers, scholars and researchers in early childhood education, education policy and education development"--
Keywords: Zhongguo fu li hui; Early childhood education -- China; Education and state -- China; Educational change -- China; Children with social disabilities -- Education -- China; EDUCATION / Evaluation; EDUCATION / Educational Policy & Reform / General; EDUCATION / Preschool & Kindergarten